2021
DOI: 10.3389/fpls.2021.646146
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Relationships Between Endophytic Bacteria and Medicinal Plants

Abstract: Plants benefit extensively from endophytic bacteria, which live in host plant tissues exerting no harmful effects. Bacterial endophytes promote the growth of host plants and enhance their resistance toward various pathogens and environmental stresses. They can also regulate the synthesis of secondary metabolites with significant medicinal properties and produce various biological effects. This review summarizes recent studies on the relationships between bacterial endophytes and medicinal plants. Endophytic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 117 publications
1
83
0
5
Order By: Relevance
“…Streptomyces spp. within Bruguiera gymnorhiza and Boesenbergia rotunda increased flavonoids and cyclopeptides with anti-HIV and anticancer activities [15]. Endophytic bacteria, as well as fungi, can produce paclitaxel [16].…”
Section: Rhizobium and Streptomyces Spmentioning
confidence: 99%
See 2 more Smart Citations
“…Streptomyces spp. within Bruguiera gymnorhiza and Boesenbergia rotunda increased flavonoids and cyclopeptides with anti-HIV and anticancer activities [15]. Endophytic bacteria, as well as fungi, can produce paclitaxel [16].…”
Section: Rhizobium and Streptomyces Spmentioning
confidence: 99%
“…Within Taxus baccata, Streptomyces produced 0.01-0.02 ng/mL, and Bacillus subtilis produced 1-25 ng/mL [16]. Indeed, as Wu et al pointed out, the relationship between medicinal plants and endophytes is a long-term, symbiotic relationship [15]. Endophytes can strongly regulate the synthesis of secondary metabolites in plants.…”
Section: Rhizobium and Streptomyces Spmentioning
confidence: 99%
See 1 more Smart Citation
“…Endophytes could produce a large amount of novel and bioactive secondary metabolites that are not only beneficial to the host plants but also economically important to humans for the potential applications in pharmaceutical, agricultural, and food industries ( Gutierrez et al, 2012 ). Studies have shown that the community structure of endophytes is affected by host plant and multiple environmental factors ( Wu et al, 2021 ). Host plants can also influence their microbiome by secreting various metabolites in plant tissue ( Pang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic microorganisms live in various tissues and organs of healthy host plants without negatively affecting the plant’s health or functions ( Wu et al, 2021 ). Endophytic microorganisms have important effects on plant growth, development and the accumulation of metabolites ( Lugtenberg et al, 2016 ; Zhou et al, 2020 ; Liu and Wei, 2021 ; Santos et al, 2021 ; Singh et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%